Problematika dan Solusi Pada Permasalahan Kemampuan Membaca Siswa Kelas Tinggi di SDN 105326 Bangun Rejo - Pane, Dian Ade Putri; Purba, Jesika Nonida; Purba, Kesia Meylani; Chaniago, Rafiqah Azizah; Zahra, Rawiyah Fatimatuz (Yayasan Daarul Huda Kruengmane, 2024)
The reading ability of students in Indonesia still shows a worrying condition. In the modern era enriched with technology, improving reading skills as a dynamic source of knowledge has not been achieved. In the field, it was found that there were differences in reading abilities between students; Some students can read fluently without any problems, while others are not able to read well. This research aims to explain the problems that occur in students who are not proficient in reading in high grades and the solutions provided. This research uses descriptive qualitative methods to analyze students' reading skills. Research subjects included 56 class 5 students from SDN 105326 Bangun Rejo, consisting of 20 class 5A students, 18 class 5B students, and 18 class 5C students, as well as teachers who taught in these classes. Primary data was collected through interviews with teachers and students as well as observing learning activities at school. Secondary data was obtained from documentation collected to strengthen the validity of the data. The research results show that optimizing classroom and school management which enables good learning facilities, creating a conducive learning environment, as well as the role of parents and the surrounding environment can increase students' awareness in maximizing their reading skills.